Potential of border tax adjustments to deter free riding in international climate agreements - Zeynep Burcu Irfanoglu; Juan P Sesmero; Alla Golub (Environmental Research Letters, 2015)
The objective of this study is to conduct assessment of the hypothesis that trade sanctions in the form of border tax adjustments (BTAs) used by the United States against China, constitute a viable enforcement mechanism to sustain compliance with a range of emissions taxes in the context of agreements to curb global emissions of greenhouse gases (GHGs). The performance of BTAs is then compared with those of punitive tariffs on the basis of the range of emission taxes that can be successfully enforced by their implementation. Results show that BTAs are a viable enforcement mechanism for international GHG mitigation agreements. However the maximum level of carbon tax that can be enforced varies dramatically with (1) the marginal damage of pollution perceived by Chinese authorities, and (2) the legal limitations that GATT rules may impose on BTAs. Finally, while BTAs seem a promising enforcement mechanism in the context of climate agreements, punitive tariffs seem to be capable of supporting a much stricter environmental target.